1991
DOI: 10.1002/ptr.2650050113
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a saikosaponin responsible for the antiinflammatory activity of Bupleurum gibraltaricum lam. Root Extract

Abstract: Bupleurum gibraltaricumLam. root extract demonstrated an antiinflammatory activity against carrageenan produced plantar oedema in the rat. We have isolated a compound responsible for this activity, a glycoside of saikogenin G containing three sugars. This compound differs from saikosaponin d in that the latter contains only two sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…(+) PGE2 production [84,92] Saikosaponin B2 (+) PGE2 production [73,84,92] (-) Human coronavirus (HCoV) replication Saikogenin D (-) PGE2 production [95] B. fruticescens Butanol extract (-) Acute inflammation [96] Methanol extract (-) 5-LOX, COX-1 [97] Essential oil (-) Acute inflammation [17] Fruticesaponin B (-) Acute inflammation [96] B. fruticosum Petroleum ether extract (-) IL-1b, IL-6, TNF-a, PGE2 [98] Essential oil (-) Acute and chronic inflammation [18,99] Oxytocin antagonism Antifungal Saikosaponin fraction Hepatoprotective against DMN [100] Morinin L (-) IL-1, IL-6, IL-8, TNF-a, NF-kB [101] Buddlejasaponin IV Hepatoprotective against DMN [100] B. gibraltaricum Methanol extract (-) Acute inflammation [102] Essential oil (-) Acute and chronic inflammation [16,19] Oxytocin antagonism Antibacterial, antifungal Saikosaponin I (-) Acute inflammation [102] B. kaoi Saponin-rich fraction Hepatoprotective against CCL4 [103][104][105][106] (-) sGOT, sGPT, AST and ALT levels (+) IFN-g level Cytotoxic against A549 cell line Water extract (+) IFN-g and GSH levels [66,105] (-) Coxsackie B1 replication Polysaccharide-rich fraction (-) sGOT and sGPT levels [105] (+) IFN-g and GSH levels…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…(+) PGE2 production [84,92] Saikosaponin B2 (+) PGE2 production [73,84,92] (-) Human coronavirus (HCoV) replication Saikogenin D (-) PGE2 production [95] B. fruticescens Butanol extract (-) Acute inflammation [96] Methanol extract (-) 5-LOX, COX-1 [97] Essential oil (-) Acute inflammation [17] Fruticesaponin B (-) Acute inflammation [96] B. fruticosum Petroleum ether extract (-) IL-1b, IL-6, TNF-a, PGE2 [98] Essential oil (-) Acute and chronic inflammation [18,99] Oxytocin antagonism Antifungal Saikosaponin fraction Hepatoprotective against DMN [100] Morinin L (-) IL-1, IL-6, IL-8, TNF-a, NF-kB [101] Buddlejasaponin IV Hepatoprotective against DMN [100] B. gibraltaricum Methanol extract (-) Acute inflammation [102] Essential oil (-) Acute and chronic inflammation [16,19] Oxytocin antagonism Antibacterial, antifungal Saikosaponin I (-) Acute inflammation [102] B. kaoi Saponin-rich fraction Hepatoprotective against CCL4 [103][104][105][106] (-) sGOT, sGPT, AST and ALT levels (+) IFN-g level Cytotoxic against A549 cell line Water extract (+) IFN-g and GSH levels [66,105] (-) Coxsackie B1 replication Polysaccharide-rich fraction (-) sGOT and sGPT levels [105] (+) IFN-g and GSH levels…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…[97] Another study with different Bupleurum species from Spain showed that the methanol extract of B. gibraltaricum and its isolated saponin (saikosaponin I) decreased carrageenan-induced inflammatory oedema in a rat hindpaw model by 50% at 5 h after intraperitoneal injection of 150 and 50 mg/kg methanolic extracts and the isolated substance, respectively. [102] Buddlejasaponin I, IV and the sulfated saikosaponin (sandrosaponin I), which were isolated from B. rigidum, exhibited a very potent in-vivo anti-inflammatory effect (1 mg/ear dose) on mouse ear oedema induced by PMA compared with the equivalent dose of indometacin. The effect of these compounds on other inflammatory parameters [109] Rotundioside F (-) Acute inflammation [109] Rotundioside A, H, I, J Cytotoxic against MK-1, HeLa and B16F10 cell lines [30,110] B. salicifolium Polyacetylenes derivatives Antibacterial [111,112] B. scorzonerifolium Acetone extract Cytotoxic against A549 cell line [113][114][115] Wogonin, eugenin, saikochromone A (-) IL-2 [50] Saikosaponin B3, bupleurosides III, VI, IX and XIII and scorzonerosides A, B, C…”
Section: B Rigidummentioning
confidence: 99%
“…Bupleurum marginatum has long been used in Asian folk medicine for the alleviation of hepatitis, cirrhosis and many other disorders associated with inflammation . Abundant work was performed on several other Bupleurum species to unveil the mechanism of their anti‐inflammatory activity . However, B. marginatum extracts, except for essential oil, were hardly studied in this context .…”
Section: Introductionmentioning
confidence: 99%
“…From the root extract diverse acetylenic compounds, monoterpenes, angelic acid esters (3), and several saikosaponins have been isolated (4,5). From the aerial part extract flavonoids and cinnamic acids have been detected (6), and from a non-polar leaf extract two new monoterpene aldehydes along with known terpenoids were characterized (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the laboratory, the anti-inflammatory activity of the essential oil (10,11) and of a root extract (4), and the in vitro antimicrobial activity of an oil sample (14) have been investigated. Some years ago we studied the oil composition from the umbel rays, stems, leaves, fruits and the whole aerial parts of B. gibraltarium harvested in the province of Jaén, southern Spain (15).…”
Section: Introductionmentioning
confidence: 99%